Contribution of health motives to cannabis use among college students. (3rd May 2020) - Chabrol, Henri; Chassagne, Jean; Bronchain, Jonathan; Raynal, Patrick; Carey, Kate B.
Abstract: Background: The Marijuana Motives Measure (MMM) is commonly used to explore the role of motives in cannabis use and related problems. A recent study suggested that a new Health motives subscale (using cannabis to improve sleep, form, energy, appetite, health) was the strongest motive associated with problematic use among high-school students. The aim of our study was to examine the predictive value of Health motives for cannabis use among college students. Method: Participants were 328 French college students who used cannabis at least once during the last six months and completed the Cannabis Use Disorder Identification Test-Revised (CUDIT-R) assessing the severity of symptoms related to cannabis use disorder (CUD) and the Marijuana Motives Mesure (MMM). Results: Twenty-two percent reached the cutoff score for likely moderate-severe DSM-5 CUD. Multiple regression analyses showed that Health motives were the strongest predictor for the severity of symptoms related to CUD relatively to all other motives. Enhancement and Expansion were also positively associated to symptoms of CUD, far more here than in previous studies among adolescents. Conclusions: This study replicates the findings of a previous study in high-school students. Health motives were found to be a strong predictor of CUD symptoms in college and high-school students which may have implication for both prevention and treatment of cannabis use problems.